The Differences in Effect Between Back Massage Therapy and Gym Ball on Back Pain in Pregnant Women Third trimester - Hasnia, Hasnia; Dinengsih, Sri (Jurnal MIDPRO, 2023)
Pregnancy is an event that occurs in a woman, starting from the fertilization process (conception) until the birth of the baby. This process causes physical, mental and social changes which are influenced by several physical, psychological, environmental, socio-cultural and economic factors. The discomfort that pregnant women often experience, especially in the third trimester of pregnancy, is back pain. The objective of the research are knowing perbedaan providing back massage and gym ball therapy for back pain in third trimester pregnant women at TPMB "S" East Jakarta 2022. This research is quantitative sense quasi experiment,with a two group pretest-posttest design. The population in this study were 43 mothers who experienced back pain at TPMB "S" with a sample size of 30 respondents consisting of 15 gym ball groups and 15 back massage group respondents using purposive sampling, namely sampling based on exclusion and inclusion criteria. The average pretest and posttest back pain scores given the gym ball were different for back pain (9.57). The average pretest and posttest back pain score given back massage is the difference in back pain (5.26), Both there were significant changes, in giving gym ball and back massage, gym ball was more effective in reducing back pain by a difference of (4.27). There is an influence between gym ball therapy and back massage in reducing back pain It is hoped that this will be taken into consideration for non-pharmacological treatment, which can be done yourself at home using the gym ball that was givengym balland back massagein reducing back pain in pregnant women who experience back pain.